The Comparison of Using Words between Enlightenment Online and Vietnamese Buddhist Temple - Nguyen Van Thao (IJECA (International Journal of Education and Curriculum Application), 2018)
Vietnamese vocabulary is divided by different criteria, such as: word classes by origin; according to the scope of use; by using style and by positive and negative criteria, specifically, the native word class is the core class in Vietnamese vocabulary, which is a prop and plays a controlling role, controlling the activities of other word classes. Identifying a word as a native word is no easy task. Because Vietnamese has a common origin with Mon - Khmer languages. Therefore, there are words that still share common words. Finding the exact origin is extremely difficult, even for linguistic historians. In addition, the scope of words usage, the southern Buddhist press is heavily influenced by the Southern dialect, this is understandable because the writers (Buddhist reporters) often come from the South and one more thing is written for southern readers. In contrast, the current use of Buddhist jargon requires an exchange, that is: speaking of the Buddhist press language, it is impossible not to mention the word class (jargon) that has its own particularity. Buddhist jargon plays a tremendous role in preserving and promoting the values of Buddhism. It is inconceivable if the Buddhist language did not have these jargon